Tata Kelola Perusahaan dan Leverage Terhadap Financial Distress Di Bursa Efek Indonesia - Go, Owen Tamashi; Wijaya, Liliana Inggrit; Muhardi, Werner Ria (Politeknik Negeri Batam, 2024)
By developing a bankruptcy model with data from non-financial sector businesses registered on IDX for the years 2017